Ogilvy on advertising - Ogilvy, David (London : Welbeck, 2023)
Everything from writing successful copy to finding innovative ways to engage people and from identifying with your audience to the various ways to sell a lifestyle, this book looks at what sells, what doesn't and why. And, in doing so, he teaches what you can do to sell the most brilliant item of all: yourself.
Includes bibliographical references and index.
Keywords: Advertising; Business